2022
DOI: 10.3390/v14061316
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Delta Variant N Gene Mutations Reduce Sensitivity to the TaqPath COVID-19 Multiplex Molecular Diagnostic Assay

Abstract: As the SARS-CoV-2 virus evolves, mutations may result in diminished sensitivity to qRT-PCR diagnostic assays. We investigated four polymorphisms circulating in the SARS-CoV-2 Delta lineage that result in N gene target failure (NGTF) on the TaqPath COVID-19 Combo Kit. These mutations were detected from the SARS-CoV-2 genome sequences that matched with the diagnostic assay results of saliva specimens. Full length N genes from the samples displaying NGTF were cloned into plasmids and assayed using three SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although the G214 and G215 deletions have already been reported to cause NGTF with the TaqPath Kit [20], our most frequent finding, the A217S mutation, has not been described until now. There are 5194 sequences containing only the amino acid substitution A217S and 3385 sequences containing both A217S and G215C that have been uploaded to GISAID as of July 2022.…”
Section: Discussionmentioning
confidence: 77%
“…Although the G214 and G215 deletions have already been reported to cause NGTF with the TaqPath Kit [20], our most frequent finding, the A217S mutation, has not been described until now. There are 5194 sequences containing only the amino acid substitution A217S and 3385 sequences containing both A217S and G215C that have been uploaded to GISAID as of July 2022.…”
Section: Discussionmentioning
confidence: 77%
“…Since dPCR relies on sequence homology between probes, primers, and template nucleic acids, it is susceptible to failure as SARS-CoV-2 evolves mutations. There have been numerous reports of SARS-CoV-2 mutations that cause failure on diagnostic RT-PCR assays ( 26 28 ). Mutations in other nucleotides of the probe or primer binding regions will result in failed amplification, as observed with the K444 reference probe against the XBB lineage ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Partial ORF1ab gene failure was once described in the BA.2.12.1 lineage of the Omicron, which contained ORF1ab synonymous mutations C11674T and T15009C [20] . Holland et al reported that C636T, T651C, 641∆6, and A638G mutations in the Delta lineage could result in N gene target failure of the TaqPath COVID-19 Combo Kit [21] . As well, the 21765 to 21770 genomic deletion (spike ∆69−70) of the Alpha variant led to S gene target failure of this kit [22] .…”
Section: Discussionmentioning
confidence: 99%